Corporate Social Responsibility and Corporate Longevity: The Mediating Role of Social Capital and Moral Legitimacy in Korea - Ahn, Se-Yeon (Journal of business ethics, 2018)
How does a company achieve long-term survival? This study starts with the question of why, among companies on the verge of bankruptcy, some survive and some break up. This study argues that the long-term survival of a company is determined by not only its economic performance but also its social performance. It clarifies that sustainable corporate social responsibility (CSR) practices facilitate long-term survival. Thus, this study analyzed 259 CSR actions performed by eight representative long-lived companies in Korea and how the various CSR actions helped these companies overcome crises and survive. The common CSR actions practiced by all the long-lived companies had a positive influence on forming social capital with primary stakeholders and securing legitimacy from secondary stakeholders, which in turn had a significant influence on maintaining survival. This study provides significant implications for the value of CSR practices that have been controversial, by presenting a model of how CSR actions facilitate corporate longevity.